Study on the practical notions of tolerance - de Jesus Silva de Sousa, Francisco; Maciel Limas , Yasmin (Seven Editora, 2023)
The practice of tolerance is essential in any society, given that diversity is a strong characteristic of the human beings that compose it. Respect for people with their different beliefs, positions, and ways of being in the world is, without a doubt, a value to be cultivated both for the dignity that is proper to each human being and for the maintenance of harmonious coexistence among them, since, man is a social being. DOI: 10.56238/pacfdnsv1-098